(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
This paper focuses on constructing the exact solutions of a (4+1)- dimensional BLMP equation via the two variables (G'/G,1/G)-expansion method and extended generalized Riccati equation mapping method. Firstly, the main ideas of the methods are described. Then, the methods are applied to the equation to derive the exact solutions including singular, kink (or anti-kink) and periodic solutions. Finally, the 3D plots of some exact solutions are observed graphically and intuitively by assigning the values of unknown parameters. The results prove that the methods are powerful, enriching the diversity of forms of exact solutions.